A new, high-elevation glassfrog (Anura: Centrolenidae) from Manu National Park, southern Peru - Catenazzi, Alessandro (2012)
We describe a new species of glassfrog from the cloud forest of Manu National Park, southern Peru, at elevations of 2750-2800 m. The new species is similar in morphology to Centrolene lemniscatum, which occurs in northern Peru at elevations of 2000-2280 m. Both species have white labial stripes, humeral spines, and lack vomerine teeth. The new species differs from C. lemniscatum by its larger size, labial stripe extending into a distinct lateral stripe instead of a discontinuous lateral stripe, snout profile inclined anteroventrally instead of bluntly rounded, greater depression in the internarial area, and by having strongly protruding nostrils. Males of the new species emit long calls with 8-14 peaked notes, instead of a short tonal note in C. lemniscatum. Another morphologically similar species, C. buckleyi, has a short advertisement call composed of 1-5 notes, and is genetically distinct from the new species. This new Centrolene extends the known distribution of Centrolene to the south by 600 km, and is the southernmost species of this genus. Copyright © 2012. Magnolia Press.